Design and Modeling of a Radiofrequency Coil Derived from a Helmholtz Structure - Ghaly, S. M. A.; Al-Snaie, K. A.; Ali, A. M. (Engineering, Technology & Applied Science Research, 2019)
This paper focuses on radiofrequency (RF) coils that can produce a high electromagnetic field homogeneity to be used for magnetic resonance imaging (MRI) applications. The proposed structure is composed of four wire loops symmetrically located on an ellipsoidal surface. The main objective of this work is to improve field homogeneity compared to a standard Helmholtz coil. Numerical simulation was carried out to assess the RF electromagnetic field behavior of the proposed coil. Different electrical modeling and simulations were investigated, particularly the study of the whole modeling of the proposed structure taking into account all the couplings between the loops. The proposed coil was evaluated and compared with the standard Helmholtz coil. Simulation and experimental results confirmed the good performance of the developed coil in terms of electromagnetic field homogeneity, efficiency, sensitivity, and quality factor.